2nd International Interdisciplinary Congress for Professionals and Students of Foreign Languages, 2025. (2025)
The II Congreso Internacional Interdisciplinario de Profesionales y Estudiantes en Lenguas Extranjeras (CIPELEX 2025) emerges as a space for academic reflection, innovation, and dialogue among researchers, teachers, students, and professionals from diverse linguistic and cultural backgrounds. Organized by the Programa Profesional en Lenguas Extranjeras of the Universidad de Cartagena, this second edition consolidates a vision that transcends disciplinary boundaries and reaffirms the vital role of languages in today’s interconnected and multilingual world. Under the central theme “Voces Globales: El papel de los profesionales y las lenguas extranjeras en un mundo multilingüe, ” the congress invited participants to rethink how language education and linguistic expertise contribute to social transformation, global cooperation, and intercultural understanding. In an era marked by digital acceleration, artificial intelligence, and transnational communication, languages have become key tools for inclusion, access to knowledge, and the promotion of ethical, intercultural, and humanistic values. Held virtually on October 2 , 2025, CIPELEX 2025 arranged national and international speakers, scholars, and students from multiple countries, Colombia, Chile, France, Spain, Russia, and beyond who shared the results of their research and pedagogical experiences. The diversity of voices and perspectives enriched the discussions, revealing the growing importance of interdisciplinarity in fields such as translation, linguistics, applied linguistics, pedagogy, cultural studies, communication, tourism, and digital education. This compilation gathers the abstracts presented during the event. Each contribution reflects a deep commitment to inquiry, creativity, and social engagement. The studies presented explore a wide range of topics: from translation, interpretation, and multilingual communication to intercultural competence, language pedagogy, and the integration of technology in education.